2020
DOI: 10.5603/cj.a2020.0089
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury determination improves risk stratification and predicts mortality in COVID-19 patients

Abstract: Background: Despite being associated with worse prognosis in patients with COVID-19, systematic determination of myocardial injury is not recommended. The aim of the study was to study the effect of myocardial injury assessment on risk stratification of COVID-19 patients. Methods: Seven hundred seven consecutive adult patients admitted to a large tertiary hospital with confirmed COVID-19 were included. Demographic data, comorbidities, laboratory results and clinical outcomes were recorded. Charlson comorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 30 publications
(37 reference statements)
4
47
0
3
Order By: Relevance
“…We conducted a meta-analysis of 11 studies (13,889 patients) that reported multivariable-adjusted associations between admission troponins above the upper reference limit and mortality [ 13 15 , 26 , 27 , 32 , 37 , 45 , 46 , 55 , 67 ]. Elevated troponins on admission were associated with an increased risk of death (RR 2.68, 95% CI 2.08–3.46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a meta-analysis of 11 studies (13,889 patients) that reported multivariable-adjusted associations between admission troponins above the upper reference limit and mortality [ 13 15 , 26 , 27 , 32 , 37 , 45 , 46 , 55 , 67 ]. Elevated troponins on admission were associated with an increased risk of death (RR 2.68, 95% CI 2.08–3.46).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the detection of a normal troponin level at hospital admission may not be considered as a sign of very low mortality risk or criteria for early discharge. The combination of troponin with other clinical information might achieve more accurate prognostication than either alone [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms behind this association may be multiple: from severe infection with SARS-CoV-2, precipitating myocardial infarction, myocarditis, heart failure, and arrhythmias as well as an acute respiratory distress syndrome and renal failure [ 33 , 34 ]; through the evolution along with multiorgan failure directly due to SARS-CoV-2-infected endothelial cells and resulting endothelitis [ 33 ]; to the potential impacts of therapies considering the likely increase in the number of ACE 2 receptors and the corresponding increase in the susceptibility [ 33 ]. Furthermore, the link between pneumonia and cardiovascular complications should be accounted for: recent studies explore/registered myocardial injury during SARS-CoV-2, secondary to type 2 myocardial infarction, a consequence of increased oxygen demand or reduced oxygen supply during respiratory failure [ 34 , 35 , 36 ]. In this scenario, cytokines microvascular activation can cause not only myocardial injury but also harm other systems involved in COVID-19 infections, including the kidneys [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, any illness onset information is valuable, especially during a pandemic, and can be followed up with appropriate testing. It is also likely that other types of physiological measurements that are obtainable from wearable devices (for example, heart rate variability, respiration rate, skin temperature, blood oxygen saturation and electrocardiogram readings) will be valuable for distinguishing illnesses caused by different infectious agents and could be used to increase diagnostic sensitivity and perhaps even predict illness severity and symptoms [24][25][26][27] . Data on reported respiratory rates and blood oxygen saturation are expected to be particularly useful in COVID-19 prediction 28 , although the disease is quite heterogeneous in its physiological presentation 29,30 , as observed in our study.…”
Section: Articlesmentioning
confidence: 99%